Measles incidence in South Africa: a six-year review, 2015-2020 - Mukhlid Yousif; Heather Hong; Susan Malfeld; Sheilagh Smit; Lillian Makhathini; Tshepo Motsamai; Dipolelo Tselana; Morubula Manamela; Mercy Kamupira; Elizabeth Maseti; Heena Ranchod; Kennedy Otwombe; et al. (BMC, 2022)
Abstract In 2012 the World Health Organization (WHO) aimed to eliminate measles in five regions by 2020. This retrospective descriptive study reviewed measles surveillance data in South Africa for the period 2015-2020 to document the epidemiology of measles and the progress made towards meeting the 2020 measles elimination goal. A total of 22,578 specimens were tested over the period 2015-2020 yielding 401 (1.8%) confirmed measles cases, 321 (1.4%) compatible and 21,856 (96.8%) discarded cases. The most affected age group was 0-4 year olds. At the provincial level, South Africa achieved adequate surveillance, defined as more than two cases of febrile rash notified annually per 100 000 popoulation, except for KwaZulu-Natal and Limpopo in 2020, probably due to COVID-19 lockdown restrictions. Of confirmed cases, only 26% were vaccinated, 3% were too young to receive vaccines, 5% were not vaccinated, and 65% had unknown vaccination status. Measles vaccine effectiveness amongst 1-4 year olds was 80%. Using the standard case definition, South Africa achieved the measles elimination target of less than one case per one million nationally in years 2015, 2016 and 2020. The years 2017 to 2019 had incidence rates exceeding one per million nationally. Using a narrow case definition, that excluded positive rubella cases, improved the indicators with only the year 2017 having an incidence rate of more than one per million. South Africa displays intermittent measles outbreaks approximately six-yearly interspersed by inter-epidemic periods in which the country meets measles elimination targets. Intense effort is needed to increase the vaccine coverage to avoid periodic outbreaks. Enhanced molecular testing of each case will be required as measles incidence declines regionally.